Climate and livestock policy coherence analysis in Burkina Faso, Niger, Rwanda, Nepal and Cambodia - Ashley, Laurie (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Feeding and nourishing a growing and changing global population in the face of rising numbers of chronically hungry people, slow progress on malnutrition, environmental degradation, systemic inequality, and the dire projections of climate change, demands a transformation in global food systems. Policy change at multiple levels is critical for catalysing an inclusive and sustainable livestock sector. Livestock in Burkina Faso, Niger, Rwanda, Nepal and Cambodia play an important role in food security, livelihoods, income, and, to various levels, GDP. The livestock sector is expected to experience significant growth in lower- and middle-income countries in Asia and sub-Saharan Africa in coming decades in response to growing demand (Enahoro et al. 2019a). Sector growth requires policy guidance to avoid increasing livestock exposure to climate risks and raising sector greenhouse gas (GHG) emissions. Guided by the Policy Coherence for Sustainable Development Framework, this analysis examines 58 climate, agriculture, livestock, development, land, and environment policies across the five countries for strength, coherence, gaps, and conflicts in addressing livestock adaptation and mitigation. The analysis examines policy language although not implementation. Policies increasingly recognise the need to prepare for climate change impacts, and to a lesser extent, reduce emissions, as evidenced by more policy ambition for livestock adaptation and mitigation in more recent policies across policy areas. While there are clear efforts to integrate livestock climate strategies, policies often fail to articulate climate risks specific to the livestock sector and to link climate risks to adaptation options. Other consistent gaps include recognition of the role of adaptation in sector growth and resilience, comprehensive mitigation strategies, and adequate consideration of adaptation-mitigation co-benefits. Further, policies often lack the targets and monitoring efforts needed to guide and measure policy impact. Building on efforts to integrate livestock and climate, addressing this range of policy gaps will create a more enabling policy environment for livestock climate action that supports sector productivity and climate-resilience while limiting emissions.